1 Korintiërs 15:49b: "n Hortatief- of futurumlesing? - Botha, S. P. (Hervormde teologiese studies, 1993)
1 Corinthians 15;49b: A hortative or future reading? The didactical context within chapter 15 of 1 Corinthians furnishes the reason why the publishers of the Greek New Testament and the majority of exegetes preferred the future textual variant (jopéaojiei/ in 1 Corinthians 15:49b instead of the hortative reading (jiopéaa)- which enjoys stronger textual support. In addition to convincing text-critical arguments, discourse analytical and exegetical arguments can be put forward to show that even writhin the textual context the hortative reading makes good sense.